Association between ChAdOx1 nCoV-19 vaccination and bleeding episodes: Large population-based cohort study. Issue 40 (24th September 2021) - Trogstad, Lill; Robertson, Anna Hayman; Mjaaland, Siri; Magnus, Per
Highlights: Novel vaccines against SARS-CoV-2 are being used globally. Serious incidents have been reported after adeno-vectored SARS-CoV-2 vaccination. The reports include severe thrombosis and thrombocytopenia. Mild bleeding is more prevalent after ChAdOx1 nCoV-19 than mRNA vaccination. Women were more often affected by mild bleeding episodes than men. Abstract: Objective: To compare prevalence of skin, nose and gingival bleedings after receipt of adeno-vectored or mRNA-vaccines against COVID-19. The hypothesis is that milder symptoms indicating altered thrombocyte function may affect a larger proportion of vaccinated individuals than the recently reported severe cases with thrombosis and thrombocytopenia. Methods: Using an ongoing large, population-based cohort study, more than 80 000 cohort participants were asked through electronic questionnaires about COVID-19 vaccination and potential side effects during weeks 11–13, 2021. The response rate was 58% (81267/138924). Among the vaccinated, 83% were female, 85% health care workers and 80% were aged 40–55 years. The prevalence of self-reported episodes of skin, nose and gingival bleedings were compared after mRNA and adenovirus-vectored vaccination. Estimates were adjusted for age, sex, occupation, previous COVID-19 infection and chronic disease. Results: Four of the 3416 subjects (0.2%) who were vaccinated with a single dose of mRNA vaccine reported skin bleeding as a side effect, as opposed to 163 of 5132 subjects (3.2%) vaccinated with a single dose of the adenovirus-vectored vaccine, OR (odds ratio) = 16.0 (95% confidence interval (CI) 7.5–34.1). Corresponding ORs for nose and gingival bleeding were 8.0 (4.0–15.8) and 9.3 (4.3–20.0), respectively. Conclusions: These findings could potentially indicate that the adenovirus-vectored vaccine may lead to mild bleeding episodes in a larger proportion of vaccinated individuals, and not only in rare cases with documented thrombosis and thrombocytopenia. Studies are needed to understand the possible mechanisms behind these observations, and to establish or refute whether they share similarities with the severe thromboembolic bleeding complications.